Hybrid nanocomposites of thermoplastic elastomer and carbon nanoadditives for electromagnetic shielding. (March 2017) - Kuester, Scheyla; Demarquette, Nicole R.; Ferreira, José Carlos; Soares, Bluma G.; Barra, Guilherme M.O.
Graphical abstract: Highlights: Hybrid nanocomposites of SEBS/GnP/CNT were prepared by melt compounding. The electrical conductivity was enhanced by 17 orders of magnitude. The higher EMI-SE was 36.47 dB (99.98% attenuation) achieved in the SEBS/GnP/CNT. Results confirm synergic effect between GnP and CNT regarding EMI-SE. Abstract: Hybrid nanocomposites of poly (styrene- b -ethylene-ran-butylene- b -styrene) (SEBS), graphene nanoplatelets (GnP), and carbon nanotubes (CNT) were successfully prepared by melt compounding for electromagnetic shielding applications. The morphologies of the carbon nanoadditives and nanocomposites were investigated by Raman spectroscopy, field emission gun scanning electron microscopy, and rheological analysis. DC electrical conductivity was assessed by two-probe and four-probe techniques. Electromagnetic interference shielding effectiveness, shielding mechanisms, and dielectric properties were conducted in the X-band microwave frequency range (8.2–12.4 GHz). The results showed that CNT had a higher affinity with the matrix, and were better dispersed than GnP. SEBS/GnP/CNT nanocomposites induced an electrical conductivity increase of 17 orders of magnitude compared to the polymer matrix. The hybrid nanocomposites presented synergic effects on EMI-SE when compared to the single-component nanocomposites (SEBS/GnP and SEBS/CNT). The maximum EMI-SE of 36.47 dB (reduction of 99.98% of the incident radiation) was achieved for the SEBS/GnP/CNT nanocomposite with 5/10 wt.% of GnP/CNT, respectively. All the hybrid nanocomposites with CNT loadings equal to or higher than 8 wt.% presented the required EMI-SE for commercial applications.